Anxiolytic-like effect of the leaves of Pseudospondias microcarpa (A. Rich.) Engl. in mice - Adongo, D.W.; Mante, P.K.; Kukuia, K.K.E.; Ameyaw, E.O.; Woode, E.; Azi, I.H. (Journal of Basic and Clinical Physiology and Pharmacology, 2016)
Pseudospondias microcarpa is a plant used for managing various diseases including CNS disorders. Previous studies showed sedative and anticonvulsant effects, suggesting possible anxiolytic activity. This study therefore assessed the anxiolytic effects of P. microcarpa hydroethanolic leaf extract (PME) in mice. In the present study, anxiolytic-like effect of the extract in behavioural paradigms of anxiety - the elevated plus maze (EPM), light/dark box (LDB), social interaction test and stress-induced hyperthermia (SIH) - was evaluated. Mice treated with PME (30-300 mg kg-1, p.o.) exhibited anxiolytic-like activity similar to diazepam in all the anxiety models used. The extract increased open arm activity (p<0.05) in the EPM as well as increasing the time spent in the lit area in relation to the time spent in the dark area of the LDB. Sociability and preference for social novelty significantly (p<0.05-0.001) increased in mice treated with PME. In the SIH paradigm in mice, both PME and the benzodiazepine receptor agonist, diazepam, significantly (p<0.05) reduced the stress-induced increase in rectal temperature. The extract did not impair motor coordination and balance in the beam walk test. Results of the present study indicate that PME possesses anxiolytic-like effects in mice. © 2016 Walter de Gruyter GmbH, Berlin/Boston.
Keywords: Anxiolytic; Elevated plus maze (EPM); Pseudospondias microcarpa; Stress-induced hyperthermia (SIH)